Emotional Stability and Perception of Job Security in the Services Sector in Malaysia (Malaysian Management Journal, 2004)
Research pertaining to the perception of job security has focused primarily on attitudinal (e.g. job satisfaction), behavioral (e.g. employee turnover), and health outcomes, while research in the area of emotional stability has largely focused on attitudinal and social consequences. However, there appear to be no reported studies that have examined the relationship between emotional stability and the perception of job security in different industries within the Malaysian context. Data from 255 employees in the information technology, financial services and education industries were collected and analyzed. Results suggest that respondents in the education industry are more stable in the emotional dimension compared to those in the finance industry and that respondents in the education sector perceive job security to be higher compared to those in the finance and IT industries. In all three industries, emotional stability was significantly associated with perception of job security (r=0.403). There is strongest correlation between emotional stability and perception of job security scores in the financial services industry. This suggests that in an industry that is unstable, respondents with higher emotional stability tend to perceive the same environment as more stable than those who have lower emotional stability.